KEJUJURAN HISTORIS BARAT DAN ISLAM - Wiranto, Erham Budi (Jurnal Dakwah, 2020)
In historical relations between the West and the Islamic world, honesty is a rare dimension. The history of West-East relations seems to be filled with bias and covered in prejudice. The negative stigma of the West towards the East, and vice versa, is still being inherited and reproduced today. Sudibyo Markus tries to present an honest and balanced historical analysis in seeing the West and Islam. This paper is a review of Sudibyo Markus' book entitled Dunia Barat dan Islam, Cahaya di Cakrawala (The West and Islam, Light in the Horizon) published by Gramedia in 2019. Dalam sejarah hubungan dunia Barat dan dunia Islam, kejujuran termasuk dimensi yang langka. Sejarah relasi Barat-Timur seolah dipenuhi bias dan berlumuran prasangka. Stigma negatif Barat terhadap Timur, demikian pula sebaliknya, masih terus terwarisi dan direproduksi hingga kini. Sudibyo Markus mencoba menghadirkan analisis sejarah yang jujur dan berimbang dalam melihat Barat dan Islam. Tulisan ini adalah telaah terhadap buku karya Sudibyo Markus berjudul "Dunia Barat dan Islam, Cahaya di Cakrawala" yang diterbitkan oleh Gramedia tahun 2019.